Improving agricultural productivity for poverty alleviation through integrated service provision with public-private sector partnerships: examples and issues - Hussain, Intizar; Perera, L.R. (International Water Management Institute, 2004)
Enduring low agricultural productivity is one of the major causes of rural poverty in South Asia. Based on a review of recent empirical studies, this paper focuses on three key questions: (1) why is agricultural productivity low in the region?; (2) what are the key constraints and opportunities for enhancing agricultural productivity; and (3) what are the effective mechanisms to improve access to key productivity enhancing technologies, factors and services. Two major points raised in the paper are: (a) improved management of land and water is important for increasing productivity, but equally important is farmers' access to non land and water-related inputs and services, which through their complementary relationships with water, increase the productivity and value of water. Even if most of the constraints related to land and water are removed through improved management, the resulting gains in productivity may not be sufficient-in the presence of constraints related to other factors and services-to have any significant impacts on poverty. Therefore, in order to generate any major increases in productivity, farmers' improved access to non land and water-related factors and services is also important; (b) access to these factors and services can be improved by providing them in an integrated manner with public-private sector partnerships. Based on examples of various models, initiatives and practices from Pakistan, India, Sri Lanka, China, Sub-Saharan Mrica and other countries, the study suggests a framework for integrated services provision in the agriculture sector, and raises key research issues and questions to be explored.